We have to find the solution of log(2)(x+1) + log(2)(x-2) = 2

log(2)(x+1) + log(2)(x-2) = 2

use log a + log b = log a*b

=> log(2) (x+1)(x-2) = 2

=> (x+1)(x-2) = 2^2

=> x^2 - x - 2 = 4

=> x^2 - x - 6 = 0

=> x^2 - 3x + 2x - 6 = 0

=> x(x - 3) + 2(x - 3) = 0

=> (x + 2)(x - 3) = 0

=> x = -2 and x = 3

As the log of a negative number is not defined eliminate x = -2.

**The required solution of the equation is x = 3.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.